Enteropathogenic and Enterohemorrhagic Escherichia coli Infections: Emerging Themes in Pathogenesis and Prevention. (2002) - Vallance, Bruce A; Chan, Crystal; Robertson, Marilyn L; Finlay, B Brett
Abstract : Enteropathogenic Escherichia coli (EPEC) and enterohemorrhagic E coli (EHEC) are important causes of infectious diarrhea, particularly among pediatric populations. While EPEC is a significant health threat in the developing world, EHEC causes sporadic but deadly outbreaks of hemorrhagic colitis and hemolytic-uremic syndrome in North America and other developed areas. The present review discusses emerging themes in the pathogenesis of EPEC and EHEC, including the discovery and characterization of novel bacterial proteins that are injected by the pathogen into host cells. Recent advances have also been made in the development of relevant animal models, while bacterial virulence factors are being investigated as potential vaccination targets for humans and animals. It is hoped that these new areas of study will not only further our knowledge of the pathogenesis of EPEC- and EHEC-induced disease but also provide opportunities for reducing infection rates and improving treatment options in the future.